Evaluation of the Impact of Collaborative Research on Robust Design Methodologies: A Large Scale Empirical Case Study with an Automotive OEM. (May 2022) - Campean, F.; Uddin, A.; Bridges, J.; Fannon, S.; Yildirim, U.
Abstract: The evaluation of impact of collaborative research on robust design methodologies and methods is important to both academic and industry stakeholders. This paper introduces a framework for impact evaluation which combines the broader framework adopted for the academic research impact assessment with the organisation viewpoint centred on business results, process improvement and product development teams capability improvement. A large scale empirical study conducted with evidence from technical reports on workplace projects from an automotive OEM proved the validity of the proposed framework.